2008
DOI: 10.1002/jnr.21964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delayed treatment with combined GDNF and continuous electrical stimulation on spiral ganglion cell survival in deafened guinea pigs

Abstract: Electrical stimulation (ES) of spiral ganglion cells (SGC) via a cochlear implant is the standard treatment for profound sensor neural hearing loss. However, loss of hair cells as the morphological correlate of sensor neural hearing loss leads to deafferentation and death of SGC. Although immediate treatment with ES or glial cell line-derived neurotrophic factor (GDNF) can prevent degeneration of SGC, only few studies address the effectiveness of delayed treatment. We hypothesize that both interventions have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 40 publications
7
67
0
1
Order By: Relevance
“…Our results partially correspond to results of previous studies showing that GDNF has a protective effect on antibiotics-induced ototoxicities (21)(22)(23)(24). Mutation of c-Ret at Y1062 has been shown to fail to respond to GDNF in vitro (19).…”
Section: Discussionsupporting
confidence: 91%
“…Our results partially correspond to results of previous studies showing that GDNF has a protective effect on antibiotics-induced ototoxicities (21)(22)(23)(24). Mutation of c-Ret at Y1062 has been shown to fail to respond to GDNF in vitro (19).…”
Section: Discussionsupporting
confidence: 91%
“…Improved EABR thresholds have also been reported after intracochlear overexpression of BDNF by adenovirus ) and intracochlear infusion of CTNF (Yamagata et al 2004) or GDNF (Maruyama et al 2008;Scheper et al 2009). Our previous study demonstrated a marked 6-dB improvement in EABR thresholds over 10 weeks of BDNF infusion in neonatally deafened, developing cats (Leake et al 2011).…”
Section: Longitudinal Eabr Threshold Datamentioning
confidence: 85%
“…While multipotent cells from other species are well characterized, data on guinea-pig-derived cells are lacking. However, the guinea pig is an important model in hearing research since its inner ear spaces are easily accessible [21][22][23] . Due to the lack of data on autologous stem cells, recent studies primarily use xenogenic stem cell applications for cellbased otological experiments in the guinea pig model [1 5] .…”
Section: Discussionmentioning
confidence: 99%